Discovery of Japan by Russia and the Crimean War - Aleksandr Yu. Petrov (Гуманитарный вектор)
In the 17th century Japan decided to pursue a policy of limiting or completely prohibiting external contacts. This policy lasted more than two centuries. During the XVIII ‒ early XIX centuries Russia made attempts to establish diplomatic and trade relations with the Land of the Rising Sun, which had only limited success. The end of the isolation policy is associated with the expeditions to Japan by E. V. Putyatin in 1853–1854. The article gives a general overview of the international situation that had developed around Japan at that time. The role of the Russian-American company in supplying the expedition of E. V. Putyatin is noted. An analysis of the negotiations between Russia and Japan is carried out, its features are shown. The Treaty of Shimoda is being studied. The article provides memoirs of contemporaries of those events. The agreement became a model for similar agreements between other countries and Japan. Simultaneously with Putyatin’s journey, the defense of Petropavlovsk-Kamchatsky took place, as part of the Crimean War. The article shows how those events influenced the establishment of relations with Japan. The article has been prepared using an interdisciplinary approach that combines historical and linguistic methods as well. Close attention is paid to publications by Japanese authors and work with archival materials, especially with documents from the Russian State Archive of the Navy, the Archive of Foreign Policy of the Russian Empire, the State Archive of the Irkutsk Region, the Manuscript Department of the Russian National Library and the electronic archive of the National Diet Library of Japan.